Light Extraction Efficiency Analysis of Flip-Chip Ultraviolet Light-Emitting Diodes With Patterned Sapphire Substrate - Yu Kee Ooi; Jing Zhang (IEEE Photonics Journal, 2018)
This study investigates polarization-dependent light extraction efficiency (ηextraction ) of AlGaN-based flip-chip ultraviolet (UV) light-emitting diodes (LEDs) emitting at 230 nm and 280 nm with microdome-shaped patterning on sapphire substrate based on 3-D finite-difference time-domain simulations. Three types of patterned sapphire substrates (PSS) have been analyzed: bottom-side PSS, top-side PSS, and double-sided PSS. Our results show that microdome-shaped patterning on sapphire substrate is predominantly beneficial in enhancing transverse-magnetic (TM)-polarized output. Specifically, TM-polarized ηextraction enhancement of up to ∼4.5 times and ∼2.2 times can be obtained for 230 nm and 280 nm UV LEDs with bottom-side PSS, respectively, and ∼6.3 times and ∼1.8 times for 230 nm and 280 nm UV LEDs with top-side PSS, respectively. By employing double-sided PSS, up to ∼11.2 times and ∼2.6 times enhancement in TM-polarized ηextraction can be achieved for 230 nm and 280 nm UV LEDs, respectively. In contrast, the microdome-shaped PSS act as a reflector for transverse-electric-polarized photons which leads to severe limitation in light extraction for both 230 nm and 280 nm flip-chip UV LEDs. Thus, it is expected that this study will serve as a guidance in designing PSS for high-efficiency mid- and deep-UV LEDs.